Sparrows and Lions: Fauna in Sikh Imagery, Symbolism and Ethics - Nesbitt, Eleanor (Religions of South Asia, 2013)
Given that the Sikhs’ scriptures – the utterances of their Gurus - are works of poetry, this article majors on the daily presence of insects, birds, fish and mammals in the recitation of the image-rich poesy that makes up the Guru Granth Sahib. Appreciation of this imagery requires understanding of the rural Punjabi context and also of earlier Indic compositions, whether sacred or secular. The introduction of certain birds and animals in Sikh parables and miracles will receive attention, and – inevitably in view of the equation of male Sikhs with Singhs (lions, or is it tigers?) – ‘big cats’ will be centre-stage. A (Quaker) poet’s bidding ‘Do not observe, become…’ will provide a stimulus to understand the more than symbolic animal presence in the Sikh universe. So too will ethical issues, centred on dietary discipline (vegetarian or non-vegetarian) and the legitimacy of hunting (the pursuit of two Gurus). Here consideration of Sikh’s relationship to the older, wider Indic matrix calls for discussion, and highlights the differentiation of groupings within the Panth with regard to meat-eating, cow-slaughter etc. Sikh tradition affords creative resources for reconnecting with the environment in the era of a dawning ecumenical attention to ecological distress, whilst at the same time Sikhs, especially in diaspora, are increasingly distanced, culturally and linguistically, from the Gurus’ imagery and from interaction with non-human animals.